TRANSLATION UNITS - Zarinabonu Ahmadjonova; Akhmedov Azimjon (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. Translation studies, particularly the theoretical idea of the "translation unit," have long been a topic of debate. This paper will examine various perspectives on this concept, contrasting it with the divide between product-oriented and process-oriented translation studies. It will be suggested that the "translation unit" can be interpreted in two ways: one that is analytical and focuses on product-based studies, and another that is more dynamic and pertains to cognitive translation studies. Except for literary translation, modern translation services are considered part of the language industry, highlighting the importance of the "translation unit" in machine translation (MT). From a historical standpoint, the concept will be linked to key issues in system design and translation quality.